649 COVID BOAST In Practice: Our Experience Implementing BOA Recommendations During the UK Coronavirus Pandemic Peak. (4th May 2021) - Hoyle, A; Iqbal, K; Henry, J; Hughes, L; Johnson, D
Abstract: Background: In anticipation of the UK coronavirus pandemic peak, BOA published new pandemic-specific guidance ("COVID BOAST") in April 2020. We describe our experience implementing this restructured T&O service in a busy DGH setting during the pandemic peak. Method: A rapid retrospective audit was conducted of all patients presenting to our T&O service in April 2020, with particular emphasis compliance with COVID BOAST. Results: Our service conducted 511 outpatient reviews, and 95 operative procedures. 94% of outpatients were treated non-operatively. We provided telephone appointments to 12.8% of follow-up patients, and 39% of new patients. 82% of patients were treated with removable casts/splints/boots. 23% of patients were discharged direct from VFC or after one face-to-face fracture clinic review. Residual deformity was consciously accepted in 13% of patients. Theatre throughput fell significantly due to pandemic precautions however, femoral neck fracture volumes remained constant. Conclusions: We demonstrate broad compliance with COVID BOAST guidance. The majority of patients were treated non-operatively, including conscious acceptance of residual deformity. Our pre-existing VFC allowed us to provide a significant number of telephone consultations, although despite the practice shift towards removable splintage, face-to-face consultations were required for clinical and/or radiological assessment. The impact of increased conservative management on patients' long-term outcomes needs further evaluation.